The anthropomorphic structures of London in contemporary British fiction - Zelezinskaya, Natalia S. (Human in the Socio-Cultural Dimension, 2023)
The article deals with the image of London as a central character in the British prose of the turn of the 20th–21st centuries. Despite the accumulated experience of describing the British capital in the Victorian and realistic novel, the writers of the late 20th – early 21st century manage to bring a new perspective on this topos by means of personification. The tendency to use personification of a topos as a key literary strategy of a work is viewed, on the one hand, from the perspective of the rapid development of the worldview paradigm of anthropocentrism, which has found application in all spheres of humanitarian knowledge. On the other hand, it is explained by art laws, since the very fact of transferring a non-anthropomorphic character from secondary to the title character gives it a certain degree of anthropomorphism. The article analysis the topic image of London in «London» (1997) by E. Rutherford, «London. The biography» (2000) by P. Ackroyd and «Capital» (2012) by J. Lanchester, as well as «Conventional» (2006) by H. Simpson. The research reveals the ways of constructing anthropomorphic figurative structures in the analysed works: physiological personification in Ackroyd’s biography, a cultural-historical excursion in Rutherford’s novel, a contemporary social snapshot in Lanchester’s one and a phenomenological reduction in H. Simpson’s story. It is noted that all the authors, to varying degrees, resort to historical and literary allusions, depersonalisation of Londoners, enumeration rows, polyphony, and eco-motifs.